The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11746-016-2828-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Kinetics of Coconut Oil in the Presence of Sorbitan Esters with Different Fatty Acid Moieties

Abstract: Sorbitan esters (SEs) are shown to strongly influence the solidification kinetics and fat crystal morphology, but not polymorphic behaviour, of coconut oil (CNO). Solid-state SEs (sorbitan monopalmitate, monostearate, and tristearate) affect both the high-and low-melting fractions of CNO by decreasing induction time and by increasing crystallization rate as well as the number concentration of crystals. Liquid-state SEs (sorbitan monoleate and trioleate) and canola oil do not specifically influence the high-or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…a) corresponds to the melting and polymorphic transformation of both phases (HTc‐α and LTc‐β′ forms into CO‐β′ form), and the following peak indicated the melting of CO‐β′. A similar crystallization behavior of CO was reported by Sonwai et al () whereby CO first crystallized into the α form followed by the β′ form during cooling from 50 to −5°C at 1°C min −1 . Takeuchi et al () found that a mixture of trilaurin and trimyristin (70:30) (as TAG representative for CO) was a miscible solid solution phase, which first crystallized into the α form (the SAXD peak at 3.7 nm and the WAXD peak at 0.42 nm), followed by transformation into the β′ form (the SAXD peak at 3.4 nm and the WAXD peaks at 0.42 and 0.38 nm).…”
Section: Resultssupporting
confidence: 70%
“…a) corresponds to the melting and polymorphic transformation of both phases (HTc‐α and LTc‐β′ forms into CO‐β′ form), and the following peak indicated the melting of CO‐β′. A similar crystallization behavior of CO was reported by Sonwai et al () whereby CO first crystallized into the α form followed by the β′ form during cooling from 50 to −5°C at 1°C min −1 . Takeuchi et al () found that a mixture of trilaurin and trimyristin (70:30) (as TAG representative for CO) was a miscible solid solution phase, which first crystallized into the α form (the SAXD peak at 3.7 nm and the WAXD peak at 0.42 nm), followed by transformation into the β′ form (the SAXD peak at 3.4 nm and the WAXD peaks at 0.42 and 0.38 nm).…”
Section: Resultssupporting
confidence: 70%
“…3a). The crystallization profile of CNO exhibited two separate exothermic peaks at 5.6 and − 1.8 °C (Sonwai et al, 2016), whereas a sharp crystallization peak at 10.5 °C with a shoulder was observed in the crystallization profile of PKS (Siew, 2001). FHPS showed one sharp melting peak at ~59 °C while CNO showed two over‐lapping melting peaks at 15.8 and 24.8 °C (Marikkar et al, 2013) and PKS exhibited one melting peak at 33.6 °C (Siew, 2001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sorbitan esters (SE's) and particularly Sorbitan tristearate (STS) are amply used as anti‐bloom agents in confectionery products containing cocoa butter and in cocoa butter substitutes (CBS) playing an important role as potential controller of crystallization. The details of the mechanism by which STS operates were extensively reported in a series of published works the more recent ones regarding, for example, crystallization kinetics of coconut oil (Sonwai et al, 2016) and of cocoa butter (Sonwai et al, 2017), structural characteristic of crystals formed in palm oil (Cebula and Smith, 1992), and epitaxial growth of fat crystals of palm mid fraction (Ishibashi et al, 2017). The mechanism of action of STS was interfering in polymorphic transformation by blocking the form V‐ > VI transformation in cocoa butter considered the cause of fat bloom (Garti et al, 1986) or affecting the crystal morphology as well as the textural properties of palm kernel oil fats (Cebula and Smith, 1992).…”
Section: Introductionmentioning
confidence: 99%